2018
DOI: 10.1016/j.celrep.2018.08.032
|View full text |Cite
|
Sign up to set email alerts
|

GPS2 Deficiency Triggers Maladaptive White Adipose Tissue Expansion in Obesity via HIF1A Activation

Abstract: SummaryHypertrophic white adipose tissue (WAT) represents a maladaptive mechanism linked to the risk for developing type 2 diabetes in humans. However, the molecular events that predispose WAT to hypertrophy are poorly defined. Here, we demonstrate that adipocyte hypertrophy is triggered by loss of the corepressor GPS2 during obesity. Adipocyte-specific GPS2 deficiency in mice (GPS2 AKO) causes adipocyte hypertrophy, inflammation, and mitochondrial dysfunction during surplus energy. This phenotype is driven by… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

9
34
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

4
5

Authors

Journals

citations
Cited by 46 publications
(46 citation statements)
references
References 52 publications
(77 reference statements)
9
34
0
Order By: Relevance
“…Clinical and anthropometric data are detailed in Supplementary Table 1 . This study was conducted in accordance with the Helsinki Declaration as previously described [ 32 , 36 ]. The Ethics Committee of CPP Ile-de-France approved the clinical investigations, and written informed consent was obtained from all of the individuals.…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Clinical and anthropometric data are detailed in Supplementary Table 1 . This study was conducted in accordance with the Helsinki Declaration as previously described [ 32 , 36 ]. The Ethics Committee of CPP Ile-de-France approved the clinical investigations, and written informed consent was obtained from all of the individuals.…”
Section: Methodsmentioning
confidence: 99%
“…GPS2 may also play a cytoplasmic role by regulating insulin signaling via AKT ubiquitination [ 35 ]. Our recent work discovered that GPS2 controls adipocyte hypertrophy in mice by repressing transcription factor HIF1α [ 36 ]. We found that dysregulation of the GPS2-HIF1α axis disrupts mitochondrial activity and predisposes to adipose tissue expansion and a pro-diabetic status.…”
Section: Introductionmentioning
confidence: 99%
“…This is exemplified by GPS2 actions in others cell types. In fact, the anti-inflammatory action of GPS2 is conserved in adipocytes by repressing CCL2 and IL6 (198,199). While the main action of GPS2 in hepatocytes is to repress the metabolic nuclear receptor PPAR-α action (200).…”
Section: Epigenetic Control Of Macrophage Polarizationmentioning
confidence: 99%
“…This epigenome-sensitive response could be controlled by abnormal activation of enhancers region leading to uncontrolled inflammation and a pro-diabetic status as we recently proposed [ 79 ]. In collaboration with Eckardt Treuter's group, we discovered that G protein pathway suppressor 2 (GPS2), a HDAC3 corepressor complex subunit, controls enhancer activity and consequently the activation of macrophages [ [79] , [80] , [81] , [82] ]. Macrophage GPS2-KO mice display a pro-inflammatory phenotype, leading to increased adipose tissue inflammation and macrophage infiltration and development of systemic insulin resistance under diet-induced obesity conditions.…”
Section: Epigenomic Regulation Of Inflammation: Importance Of Enhancementioning
confidence: 99%